Effect of selected strains on physical and organoleptic properties of breads. (15th March 2019) - Yu, Yafang; Wang, Li; Qian, Haifeng; Zhang, Hui; Li, Yan; Wu, Gangcheng; Qi, Xiguang; Xu, Meijuan; Rao, Zhiming
Highlights: Selected strains were used as mono-culture or co-culture for sourdoughs. Texture and acidity of sourdough breads were strain-dependent. The starter strains and their interactions influenced the porosity of bread crumb. The MC4 sourdough could replace spontaneous sourdough for improving bread qualities. Abstract: The use of selected Saccharomyces cerevisiae PS7314, Lactobacillus rossiae NOS7307, Lactobacillus brevis NOS7311, and Lactobacillus plantarum NOS7315 as mono-culture or co-culture for production of sourdoughs, their breads showed different physical and organoleptic properties. The pH of breads fermented with sourdoughs incubated with mono-culture or co-culture all decreased. An opposite trend was found for TTA. The use of single lactobacillus for the dough fermentation decreased the specific volume of bread, which was 4.15–19.10% lower than that of control bread (CB). However, the synergetic fermentation helped the improvement of bread quality. Compared to CB, the mixed culture 4 sourdough remarkably decreased the hardness by 52.08%, increased the specific volume by 5.29%, improved porosity of final product by 24.90%, and gave a preferable sensory characteristic to bread. Thus, the MC4 could be recommended for replacing spontaneous sourdough for improving the quality of bread.